Lucian's science fiction novel, True histories : interpretation and commentary - Georgiadou, Aristoula. (Mnemosyne, Supplements, 1998)
This is the first substantial commentary on Lucian's Verae Historiae (\'True Histories\'), a fantastic journey narrative considered the earliest surviving example of Science Fiction in the Western tradition. The Introduction situates the work in the context of Lucian's oeuvre, especially his preoccupation with distinguishing truth from fiction and exposing the lies of philosophers. In their commentary, the editors trace the sources and the meaning of the numerous intertextual allusions and parodies of philosophers, poets, historians and paradoxographers. The Verae Historiae emerges from this scrutiny as a remarkably complex text with some very \'modern\' concerns: it problematizes the act of reading, allegorical interpretation, authorial reliability, and the validity of cultural norms and literary genres.